Are Politically Engaged Woman Participation Gender-Based, Equally and More Democratic on Policies? A Glimpse From Timor-Leste - Silva Belo, Joao da (Indonesian Journal Publisher, 2025)
Timor Leste's diverse national literature alongside western literature on women's participation in politics is still in the midst of an equitable and democratic transition. It is assumed that women's participation in politics will create a committed force towards the renewal of democratic values. Sadly, there has been a lot of injustice in the participation system in young democracies with a tradition of contributing interventions outside the government system itself such as the role of NGOs and the UNs for woman development and participation in Timor-Leste. Therefore, this article aims to introduce the extent of women's participation in electoral politics in gaining parliamentary seats. Do the nation's democratic values and public policy tendencies in the national policy realm lend support to the significance of non-conventional political participation and support for democracy internationally. This study digests and reviews the tendency of political interest, the desire to have political knowledge, the understanding of the extent of the equality of women participants in politics (elections), and also the interpersonal belief in the nuances and moralization of democracy from the perspective of gender equality.